Pathogenesis, diagnosis and treatment of primary renal well-differentiated neuroendocrine tumors: a review of the literature - Zhang, Zhongqi; Luo, Chenming; Yuan, Tengfei; Ge, Pinxu; Li, Faping; Fan, Yanpeng (Frontiers in Oncology, 2024)
Neuroendocrine tumors (NETs) are a rare type of neoplasm that originate from neuroendocrine cells and peptide neurons. Primary renal well-differentiated NETs are extremely rare, and only a few cases have been reported worldwide. In this study, we present a new case of primary renal well-differentiated NET at our institution, followed by a literature review. A systematic search was conducted using various search terms to identify relevant literature on primary renal well-differentiated NETs from 2021 to present. The study analyzed the clinical features, age, gender, tumor size, location, gross pathology, light microscopy, and immunohistochemical results of 32 cases of primary renal well-differentiated NETs. The findings suggest that these tumors are rare and have nonspecific clinical and imaging features. The diagnosis heavily relies on immunohistochemical analysis. Primary renal well-differentiated NETs are associated with low malignant potential and a favorable prognosis. Surgical resection is the preferred treatment, and long-term follow-up is necessary to monitor the patient’s condition.